2000
DOI: 10.1016/s0194-5998(00)70149-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved canine model for laryngotracheal stenosis☆☆☆★★★

Abstract: Laryngotracheal stenosis (LTS) is a serious challenge for the otolaryngologist. Although progress has been made in preventing and treating LTS, more research is required. Existing canine models for LTS incur high mortality and morbidity, require relatively complicated procedures or costly equipment, entail lengthy waiting periods, or have unpredictable results. A simple, reliable, and inexpensive procedure, requiring no tracheotomy, is described for creating a canine model for LTS research. The new improved mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…Electrocoagulation was chosen because it is a safe and easily reproducible method and there is a good availability of technically capable individuals to create the required equipment, such as the extremity used for electrocoagulation and the self-interruption system. Results obtained with this method are similar to those found in other studies [19,20,24]. During the study no technical difficulty was observed and the time needed to conduct each procedure was small with no need of anesthetic complementation and no complication associated to the technique.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Electrocoagulation was chosen because it is a safe and easily reproducible method and there is a good availability of technically capable individuals to create the required equipment, such as the extremity used for electrocoagulation and the self-interruption system. Results obtained with this method are similar to those found in other studies [19,20,24]. During the study no technical difficulty was observed and the time needed to conduct each procedure was small with no need of anesthetic complementation and no complication associated to the technique.…”
Section: Discussionsupporting
confidence: 86%
“…The direct lesion of the mucosa of the subglottic region due to abrasion [17,18], the applications of chemical agents [19] or endoscopic-controlled electrocoagulation [20] are the experimental techniques mostly used. However, even though there are various SGS experimental induction endoscopic models, there is still no consensus about the ideal model [21].…”
Section: Introductionmentioning
confidence: 99%
“…Electrocautery as an electrosurgical technique has been used widely in models to induce airway stenosis [4][5][6]. The approach was chosen to induce airway stenosis because it is a relative fast, precise, quantifiable, and reproducible method [5]. Radiofrequency operation and electrocautery are both electrosurgical techniques that damage the tissue by thermal lesion and the use of radiofrequency has all the advantages of electrocautery.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been used to induce a model of airway stenosis that include long-term endotracheal intubation [2], laser cauterization [3], electrocautery [4][5][6], brushings [7], and the application of a cauterant such as hydrochloric acid [4], silver nitrate [4] or ethanol [6]. However, these methods are associated with a range of variables such as inaccurate and unpredictable results, complicated and difficult operations, and severe injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation